“I Put Myself Back in the Narrative”: Hamilton as Founders Fanfiction - Jeremy Brett (European Journal of American Studies)
Scholars and critics that gauge Lin-Manuel Miranda’s hit musical Hamilton in terms of its historical accuracy or inaccuracy miss the point about Miranda’s creative endeavor. Hamilton represents a highly visible example of what might be called “Founders fanfiction”; although the musical is rooted deeply in historical fact, primarily via Ron Chernow’s magisterial biography of Hamilton, nonetheless, as a narrative the production is a piece of popular wish-fulfilment. Certainly, the show elides or ignores some of his more unpalatable characteristics, such as his deep elitism and love of military display and power. The elaboration of certain aspects of one’s character over another is a practice common to the creative endeavor of fanfiction. In fanfic, writers often create idealized or otherwise fantastical versions of beloved media characters, placing them in situations unreflective of the traditionally established narrative. This practice lets fanfic creators craft their own narratives with their own sense of agency and identity and make them more meaningful. Miranda performs the same kind of narrative reshaping of Hamilton’s life to conform to a particular view of Hamilton, much as historians and authors before him have done in the creation of what is known as “Founders chic”—the stressing of American Founders’ virtues and character at the expense of historical dimensionality and reality. Furthermore, the play has itself become a source of multiple instances of fanfiction, signifying significant emotional connections in the story that reflect Miranda’s own self-identification with Hamilton.